Session RPE following interval and constant-resistance cycling in hot and cool environments - Green, J. M.; Yang, Z.; Laurent, C. M.; Davis, J. K.; Kerr, K.; Pritchett, R. C.; Bishop, P. A. (Medicine & Science in Sports & Exercise, 2007)
Purpose: This study examined effects of heat gain, circulatory adjustment to temperature regulation (HR), and [La] consequent to interval (INT) and constant-load (CON) cycling on session RPE (S-RPE).